Man As a Meter. - Snoonian, Deborah (Architectural Record, 2002)
Focuses on an audiovisual research at the University of Michigan. Importance of collecting qualitative and quantitative data in improving sound and light design; Composition of the audio system; Details on the spectral distribution of each different sound.